Pinning control of spatiotemporal chaos in the LCLV device - Carolina Mendoza; Jean Bragard; Pier Luigi Ramazza; Javier Martínez-Mardones; Stefano Boccaletti (Mathematical Biosciences and Engineering)
We study the feasibility of transferring data in an opticaldevice by using a limited number of parallel channels.By applying a spatially localized correcting term to theevolution of a liquid crystal light valve in its spatio--temporalchaotic regime, we are able to restore the dynamics to a specifiedtarget pattern. The system is controlledin a finite time. The number and position of pinning pointsneeded to attain control is also investigated.